Sufism in Malaysia and its impact on the revival of the Islamic Dawah - Amr Mohamed Sayed Imam; Mohamed Ebrahim El-Sherbiny Sakr (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
There is no doubt that the science of Sufism became an essential part of our Islamic heritage, although it was not popularized as a term and concept until the third century AH.The science of Sufism focused on the spiritual aspect of the heart. The purification of the soul and the soul is the basis of the science of Sufism. Therefore, this aspect had a great impact on Islamic societies, especially Malaysian society. Who was affected by some mystical manifestations, such as wirds and remembrances, and other Islamic rituals, and passed on from generation to generation, and the persistence of it had an effect on the survival of Islam on the souls of the youth and the young, men and women, and it also had an evident effect on non-Muslims, who are many. They are destined to live among Muslims.Therefore, the primary objective of this study was: An observation of some Sufi manifestations that had a good effect in Malaysian society, and the preservation of these aspects that are the piety of hearts, as well as the rooting of these manifestations from the legal point of view and responding to the suspicions that were raised about them.